Hypoxanthine deregulates genes involved in early neuronal development. Implications in Lesch‐Nyhan disease pathogenesis. Issue 6 (5th May 2015) - Torres, R. J.; Puig, J. G.
Abstract: Neurological manifestations in Lesch‐Nyhan disease (LND) are attributed to the effect of hypoxanthine‐guanine phosphoribosyltransferase (HPRT) deficiency on the nervous system development. HPRT deficiency causes the excretion of increased amounts of hypoxanthine into the extracellular medium and we hypothesized that HPRT deficiency related to hypoxanthine excess may then lead, directly or indirectly, to transcriptional aberrations in a variety of genes essential for the function and development of striatal progenitor cells. We have examined the effect of hypoxanthine excess on the differentiation of neurons in the well‐established human NTERA‐2 cl.D1 (NT2/D1) embryonic carcinoma neurogenesis model. NT2/D1 cells differentiate along neuroectodermal lineages after exposure to retinoic acid (RA). Hypoxanthine effects on RA‐differentiation were examined by the changes on the expression of various transcription factor genes essential to neuronal differentiation and by the changes in tyrosine hydroxylase (TH), dopamine, adenosine and serotonin receptors (DRD, ADORA, HTR). We report that hypoxanthine excess deregulate WNT4, from Wnt/β‐catenin pathway, and engrailed homeobox 1 gene and increased TH and dopamine DRD1, adenosine ADORA2A and serotonin HTR7 receptors, whose over expression characterize early neuro‐developmental processes.